MODEL PEMBELAJARAN KONTEKSTUAL DALAM PENINGKATAN KEMAMPUAN BERPIKIR KRITIS BELAJAR BIOLOGI SISWA DI SMA MUHAMMADIYAH 11 PADANGSIDIMPUAN - Tuah, Sahlan (Universitas Muhammadiyah Tapanuli Selatan, 2024)
The purpose of this study is to determine the improvement of critical thinking learning skills, increase in student biology learning activities, improve the management of biology learning through the application of contextual learning models on plantae material in grade X of SMA Muhammadiyah 11 Padangsidimpuan. The validation of the second cycle test above shows that from the questions prepared, 5 questions are invalid and 10 questions are valid according to the calculation. in the first cycle an average score of 74.32 was obtained with the number of students who completed it as many as 18 people and the remaining 7 students were declared incomplete with the applicable KKM score of 75, then the PKK score of the overall learning outcomes of the first cycle was 72.02%. In the second cycle, an average score of 78.4 was obtained with the number of students who completed reaching KKM, namely 75 was 21 people and the remaining 4 people were declared incomplete, obtained by PKK in the second cycle was 84.18% categorized (Very Good).